Experiences of patients with multimorbidity with primary care and the association with patient activation: a cross-sectional study in Germany. Issue 8 (8th August 2022) - Breckner, Amanda; Glassen, Katharina; Schulze, Josefine; Lühmann, Dagmar; Schaefer, Ingmar; Szecsenyi, Joachim; Scherer, Martin; Wensing, Michel
Abstract : Objectives: This study aimed to explore the association between patient activation and patients' experience of care among an elderly multimorbid population in Germany. Design: Cross-sectional study. Setting: Primary care practices in two German settings. Participants: 346 patients with 3 or more chronic conditions aged 65 years and over from 36 primary care practices. Outcome measures: Patient activation was measured with the patient activation measure (PAM). To assess patient experiences with primary care, a set of questions concerning domains of primary care were included. Multilevel regression analyses were performed to examine which domains of care were associated with patient activation. Results: Out of 1243 invited patients, a total of 346 took part in the study (participation rate 27.8 %). Mean PAM score was 76.1. Across all patients, 3.8% achieved PAM level 1, 7.5% level 2, 27.2% level 3% and 60.7% level 4. PAM scores suggest a highly activated patient group. In the regression analysis, three out ten domains of patients' experiences showed an association with patient activation. The domains 'being involved in decision as much as desired' (B=−8.56, p=0.012) and 'receiving a self-management plan' (B=6.51, p=0.051) were associated with higher patient activation scores. Patients with an up-to-date medication plan had lower patient activation scores (B=−12.01, p=0.041). Conclusion: Specific domains of primary care were found to be associated with patient activation. To enhance patient activation, primary care physicians may increase involvement of patients in decisions. Future research should examine the causality of these associations. Trial registration number: DRKS00015718.